O ensino superior no Centro Estadual de Educação Tecnológica Paula Souza: sujeitos, experiências e currículo (1969-1976) - Broti, Marcelo Peralli (2012)
The research analyzed the history of the State Center for Technological Education Paula Souza (CEETEPS), between the years 1969 to 1976. We examined the first curriculum of the institution, within the mentioned period, emphasizing the relationship between curriculum and context. In addition, the survey sought to identify individuals who played important role in the institutional trajectory CEETEPS. The selected fonts are stored in the Document Management Center of the institution (CGD). The documentation has been analyzed from different types located in the collection. The analysis was based on theoretical references that discuss the curriculum and its relations with society, with emphasis on ideas and categories, and Michael W. Ivor F.Goodson Apple, in addition to the theoretical framework developed by the English historian EP Thompson. Inserted within the framework of social and economic transformations of the state of Sao Paulo in the early 1970s, the institution was an important vehicle for development policy of the state government in the period highlighted. Its curriculum was in line with situation university reform of 1968, based in many ways, in the human capital theory